Fluid Therapy For Pediatric Patients With Diabetic Ketoacidosis: Current Perspectives - Jayashree M (Dove Medical Press, 2019)
Muralidharan Jayashree, Vijai Williams, Rajalakshmi Iyer Division of Pediatric Emergency and Intensive Care, Department of Pediatrics, Advanced Pediatrics Centre, Post Graduate Institute of Medical Education and Research, Chandigarh, IndiaCorrespondence: Muralidharan JayashreeDivision of Pediatric Emergency and Intensive Care, Department of Pediatrics, Advanced Pediatrics Centre, Post Graduate Institute of Medical Education and Research (PGIMER), Chandigarh, IndiaTel +91 172 275 5311Fax +91-172-2744401Email mjshree@hotmail.comAbstract: Diabetic ketoacidosis (DKA) is a preventable life-threatening complication of type 1 diabetes. Fluids form a crucial component of DKA therapy, goals being the restoration of intravascular, interstitial and intracellular compartments. Hydration reduces hyperglycemia by decreased counter-regulatory hormones, enhanced renal glucose clearance and augmented insulin sensitivity. However, for the last several decades, fluids in DKA have been subject of intense debate owing to their possible role in causation of cerebral edema (CE). Rehydration protocols have been modified to prevent major osmotic shifts, correct electrolyte imbalances and avoid cerebral or pulmonary edema. In DKA, a conservative deficit assumption ranging from 6.5% to 8.5% is preferred. Normal saline (0.9%) has been the traditional fluid of choice, for both, volume resuscitation and deficit replacement in DKA. However, the risk of AKI with its liberal chloride content remains a contentious issue. On the other hand, balanced crystalloids with restricted chloride content need more exploration in children with DKA, both with respect to DKA resolution and AKI. Although fluids are an integral part of DKA management, a fine balance is needed to avoid under-hydration or over-hydration during DKA management. In this narrative review, we discuss the current perspectives on fluids in pediatric DKA.Keywords: fluids, diabetes, ketoacidosis, pediatrics, children